Observational and genetic association of non-alcoholic fatty liver disease and calcific aortic valve disease - Hao, Qing-Yun; Zeng, Yu-Hong; Lin, Ying; Guo, Jing-Bin; Li, Shi-Chao; Yang, Ping-Zhen; Gao, Jing-Wei; Li, Ze-Hua (Frontiers in Endocrinology, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) has emerged as a predominant driver of chronic liver disease globally and is associated with increased cardiovascular disease morbidity and mortality. However, the association between NAFLD and calcific aortic valve disease remains unclear. We aimed to prospectively investigate the association between NAFLD and incident aortic valve calcification (AVC), as well as its genetic relationship with incident calcific aortic valve stenosis (CAVS). Methods: A post hoc analysis was conducted on 4226 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) database. We employed the adjusted Cox models to assess the observational association between NAFLD and incident AVC. Additionally, we conducted two-sample Mendelian randomization (MR) analyses to investigate the genetic association between genetically predicted NAFLD and calcific aortic valve stenosis (CAVS), a severe form of CAVD. We repeated the MR analyses by excluding NAFLD susceptibility genes linked to impaired very low-density lipoprotein (VLDL) secretion. Results: After adjustment for potential risk factors, participants with NAFLD had a hazard ratio of 1.58 (95% CI: 1.03–2.43) for incident AVC compared to those without NAFLD. After excluding genes associated with impaired VLDL secretion, the MR analyses consistently showed the significant associations between genetically predicted NAFLD and CAVS for 3 traits: chronic elevation of alanine aminotransferase (odds ratio = 1.13 [95% CI: 1.01–1.25]), imaging-based NAFLD (odds ratio = 2.81 [95% CI: 1.66–4.76]), and biopsy-confirmed NAFLD (odds ratio = 1.12 [95% CI: 1.01–1.24]). However, the association became non-significant when considering all NAFLD susceptibility genes. Conclusions: NAFLD was independently associated with an elevated risk of incident AVC. Genetically predicted NAFLD was also associated with CAVS after excluding genetic variants related to impaired VLDL secretion.